2009
DOI: 10.1177/1079063209346699
|View full text |Cite
|
Sign up to set email alerts
|

Does Victim Age Differentiate Between Perpetrators of Sexual Child Abuse? A Study of Mental Health, Psychosocial Circumstances, and Crimes

Abstract: To test the theory that sexual offenders who abuse very young children (0-5 years) have more severe mental health and psychosocial problems than those who victimize older children, authors compared psychiatric diagnoses, social circumstances, and crime-related data in all sexual offenders against minors referred to forensic psychiatric investigation in Sweden during a 5-year period. Thirty-one men had committed index crimes involving victims between the ages of 0 and 5 years (Group 1), 90 had 6-to 11-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
1
19
1
1
Order By: Relevance
“…We explored this question without stating directional hypotheses, as prior findings based on offline offenders have been inconsistent regarding the increase of psychosocial impairments with decreasing victim age (Carlstedt et al, 2009;Firestone, Dixon, Nunes, & Bradford, 2005;Kalichman, 1991).…”
mentioning
confidence: 99%
“…We explored this question without stating directional hypotheses, as prior findings based on offline offenders have been inconsistent regarding the increase of psychosocial impairments with decreasing victim age (Carlstedt et al, 2009;Firestone, Dixon, Nunes, & Bradford, 2005;Kalichman, 1991).…”
mentioning
confidence: 99%
“…As for victim gender, Leclerc et al (2009) argued that if an offender targeted a male child as victim, it was less likely that the offender's ultimate goal was genital penetration, while adult male victims were more likely to sustain physical injuries, such as rectal trauma (Erickson et al, 1988). However, the prevalence of penetration was found to be common in both children aged between 0-5 years old (both boys and girls) and the older victims (higher proportion of boys than the other groups; Carlstedt et al, 2009), which indicated the indiscriminating characteristic of small children with regard to their gender.…”
Section: Sexual Fantasymentioning
confidence: 94%
“…In other words, victims' gender has been neglected in comparison to age in the study of child molestation. Among pre-school age victims (i.e., children age of seven and less), the reason for younger children being targets of sexual abuse was not because of their gender, but because of their small physical stature (Carlstedt et al, 2009;Erickson et al,1988;Finkelhor & Williams, 1988). It may be necessary to take a different approach to sexual offences involving older victims, when examining offending patterns and offender behaviors at the physical contact stage.…”
Section: Overview Of Sexual Violence Studiesmentioning
confidence: 99%
See 2 more Smart Citations